Building Competitive Advantage of Educational Institutions through Nature Leadership - Dian, Dian; Kusumah, Nurvina Intan; Faidah, Nida Husnul; Zahra, Sintia Rahmah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the nature of leadership in building a competitive advantage in educational institutions to win the competition between institutions. The location of research was carried out at three academic institutions with different cultures but having the same strategy in advancing their educational institutions, which are located in the province of West Java. A qualitative approach to the type of case study is used to reveal phenomena in the field. Interviews, observations and documentation are used as media to collect data. Data analysis is done through data reduction, data display, and conclusion. The research results show that; the three institutions use the nature of leadership in building competitive advantage through precise and effective strategies. Strengthening commitment, work ethic, sheer effort and maintaining partnerships is an effective strategy for leadership in managing their organization. This research provides implications about the importance of competencies, skills and other complementary aspects that a leader must possess in managing his organization to be the best of some of his competitors.